Nanowires Recent Advances - Peng, Xihong (IntechOpen, 2012)
One dimensional nanoscale structures such as nanowires have drawn extensive research interests in recent years. The size miniature brings unique properties to nanowires due to quantum confinement. The large surface-to-volume ratio renders nanowires with high sensitivity to surface effects. The unique geometrical advantages and properties facilitate the utilization of nanowires in nano-electronics. InTech scientific publisher has initialized a series of books focusing on fundamental research in nanowires, which largely boosted the widespread of knowledge among the research society. This book is intended to provide an updated review on the applications of various nanowires and the associated advancements in synthesis and properties characterization. The topics include recent progress in metal oxide nanowires, silicon nanowires, carbon based nanotubes and nanowires.